The influence of mechanical mold vibration on temperature distribution and physical properties of Al-11.8%Si matrix composites - Sayuti, M.; Sulaiman, Shamsuddin; Baharudin, B. T. Hang Tuah; Mohd Ariffin, Mohd Khairol Anuar (2012)
Mechanical vibration was introduced into the Aluminum alloy matrix composite during solidification process. The cooling curves of composite with mechanical vibration were measured and compared without mechanical vibration. The thermal conductivity and thermal diffusivity properties of the Al/TiC composite were investigated. The result indicated that the mechanical vibration reduces the temperature in homogeneity of melt. The density of the composite with 10.2, 12, 15Hz and 16 Hz of mechanical vibration improved apparently compared with the composite without mechanical vibration. The thermal conductivity and thermal diffusivity properties of composites with mechanical vibration are also both improved significantly.